330 Gender Differences in Mortality After Stroke in Thai Patients. a National Cohort Study. (19th August 2022) - Abdel-Fattah, AR; Pana, T; Tiamkao, S; Sawanyawisuth, K; Kasemsap, N; Mamas, M; Myint, P
Abstract: Aim: Gender differences in patients hospitalised with stroke is a major public health concern carrying important implications to service provision. There has not yet been a study specifically focussing on patients in Thailand. We aimed to assess the gender differences in mortality following ischaemic-stroke (IS) and haemorrhagic-stroke (HS) in a large Thai-cohort. Method: All stroke admissions of patients between 2004–2015 were included from a Thai national-insurance database. The association between gender and mortality by stroke-type was assessed at one, 12 and 60-months using multivariable Cox-regression models. Results: There were 543, 763 patients included women made up 46.6% of patients with IS (n=172, 800) and 41.3% of patients with HS (n=69, 828). Women were older than men in both IS and HS groups (mean age:67.1, SD(13.4) vs. 64.1(12.9) and 64.2(14.3) vs. 59.1(13.9)), respectively. Women had higher prevalence of comorbidities and stroke-specific risk factors compared to men. When comparing mortality by stroke-type, mortality was higher in women post-IS at one-month (HR:1.17, 95%CI:1.15–1.20), one-year (HR:1.10, 95%CI:1.09–1.12) and five-years follow-up (HR:1.02, 95%CI:1.01–1.03). Similarly, mortality post-HS was also higher in women at all three follow-up timepoints (one-month HR:1.08, 95%CI:1.06–1.10, one-year HR:1.04, 95%CI:1.03–1.06, and five-years HR:1.09, 95% CI:1.08–1.11). Conclusions: In Thai patients hospitalised with stroke, women have a greater burden of stroke-specific risk factors. The mortality outcome of women with stroke is consistently higher than that of men, which appears to be irrespective of stroke-type or duration following stroke, up to five-years after discharge. Whether this difference is attributable to differences in management or physiology warrants further evaluation.